Generation, Characterization and Collection of Solid Waste - A Case Study - Siddiqui, Dr. Lubna (IJRDO-Journal of Applied Science, 2015)
The study deals with generation and characterization of solid waste in class II town ofdistrict Ambedkar Nagar, Uttar Pradesh. With an average waste generation rate of 0.350kg/head/day, the town generates about 28.672 ton of waste daily. As per our estimatesnearly 63.95 per cent population generates 75.38 per cent waste at the rate of more than0.300 kg/head/day and only 11.77 per cent population generates less than 0.25kg/head/day. The share of organic waste is well below 50 per cent. The average organicwaste generation rate is 0.158 kg/head/day, whereas average inorganic waste generation is0.198 kg. Only 35 per cent waste is collected.